The influence of Reynolds number on the triple point trajectories at shock reflection off cylindrical surfaces. (10th January 2014) - Kleine, H.; Timofeev, E.; Hakkaki-Fard, A.; Skews, B.
Abstract In the unsteady process of shock reflection off convexly curved surfaces, the Reynolds number can have an influence on the development of the irregular reflection pattern. Time-resolved visualizations of the reflection process and high-resolution numerical simulation are used in this investigation to quantify this influence, which manifests itself in a delayed growth of the shock pattern with decreasing Reynolds number. In order to conduct reliable and unambiguous measurements, the present study concentrates on observing the development of the established irregular reflection pattern rather than attempting to determine the transition point directly. It can be seen that the influence of the Reynolds number is highly nonlinear and that changes of two orders of magnitude or more are required to produce a reliably measurable difference in the triple point trajectories, which is considerably more than what has so far been reported in the literature. The results allow one to make inferences regarding the transition process and they help to clarify previously reported discrepancies between predicted and experimentally determined transition angles.